Social spending and democracy: some evidence from South America - Gil, Ricard; Mulligan, Casey B. (Estudios de Economía, 2016)
Social spending programs are important political issues, and it would be interesting to know how political systems affect the amount spent by the public sector. Much of the cross-country data is difficult to interpret, because richer countries simultaneously have different political systems (they tend to be more democratic) and more generous government budgets for old age, medical, and other social programs. Since South American countries seem to have a much weaker association between economic and political situations, we can mitigate this collinearity by comparing South American countries with each other and with the world. All of our data show that democracies spend the same or somewhat less on social programs as economically and demographically similar nondemocracies. Pension spending has grown relative to nonpension social spending (1960-90), but some of our evidence suggests that this change in the composition of spending has been more pronounced in countries that were initially nondemocratic.